2010
DOI: 10.1063/1.3418556
|View full text |Cite
|
Sign up to set email alerts
|

Dark Schrödinger solitons and harmonic generation in left-handed nonlinear transmission line

Abstract: In this paper, we analyze the wave propagation in a practical left-handed nonlinear transmission line with series nonlinear capacitance composed of two back-to-back connected varactor diodes. Detailed circuit analysis of the transmission line shows that by properly choosing the circuit parameters, the equation governing the wave envelope evolution can be reduced to a one-dimensional nonlinear Schrödinger equation, which supports dark solitons propagation. By transient circuit simulation, the soliton evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
2
31
0
3
Order By: Relevance
“…In recent years, tunable metamaterials have attracted intensive attentions due to their particular applications in optical switching, nonlinear modulation, and so on [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. The common mechanism is to introduce certain controllable materials or lumped elements into the metamaterial units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, tunable metamaterials have attracted intensive attentions due to their particular applications in optical switching, nonlinear modulation, and so on [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. The common mechanism is to introduce certain controllable materials or lumped elements into the metamaterial units.…”
Section: Introductionmentioning
confidence: 99%
“…People also find in the transmission line metamaterials, varactor diodes can give rise to the tunability as they are very sensitive to a low direct current voltage, for instance, leaky-wave antenna with tunable radiation angle and beamwidth, tuneable directional coupler, and so on [51][52][53][54][55]. Specifically, transmission line metamaterials with varactor diodes can even serve as model systems for investigating several nonlinear phenomena in negative-index metamaterials, like asymmetric parametric amplification, abnormal pulse formation, dark schrodinger solitons and harmonic generation [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…We see clearly that the form of the solution depends on certain parameters, and this agrees with ref. [15,16,17]. The existence of soliton envelopes, kink solitons in the JNLHTL is confirmed.…”
Section: Resultsmentioning
confidence: 62%
“…III) we use a value for the initial voltage equal to V 0 = 0.5 V (in physical units). For such a value of the voltage (similar, and even smaller, values have also been used in relevant experimental works [29][30][31][32][33][34]), it can be found that…”
Section: A the Nonlinear Lattice Modelmentioning
confidence: 99%
“…[31] and the relevant work of Ref. [32]); moreover, analytical approximations, based on a continuum nonlinear Schrödinger (NLS) equation, allowed the description of bright [32,33] or dark [32,34] envelope solitons observed in the experiments.…”
Section: Introductionmentioning
confidence: 99%